(untitled) - Cavanaugh, John C; Blanchard-Fields, Fredda
Includes bibliographical references and indexes.; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Adulthood -- Physiological aspects; Adulthood -- Psychological aspects; Aging -- Physiological aspects; Aging -- Psychological aspects; Aging -- Social aspects; Thanh niên trưởng thành -- Khía cạnh tâm lý; Người cao tuổi -- Khía cạnh sinh lý